Thermodynamic Molecular Switch in Sequence-Specific Hydrophobic Interaction: Two Computational Models Compared - Paul Chun (The Scientific World Journal)
We have shown in our published work the existence of a thermodynamic switch in biological systems wherein a change of sign in ΔCp°(T)reaction leads to a true negative minimum in the Gibbs free energy change of reaction, and hence, a maximum in the related Keq. We have examined 35 pair-wise, sequence-specific hydrophobic interactions over the temperature range of 273–333 K, based on data reported by Nemethy and Scheraga in 1962. A closer look at a single example, the pair-wise hydrophobic interaction of leucine-isoleucine, will demonstrate the significant differences when the data are analyzed using the Nemethy-Scheraga model or treated by the Planck-Benzinger methodology which we have developed. The change in inherent chemical bond energy at 0 K, ΔH°(T0) is 7.53 kcal mol-1 compared with 2.4 kcal mol-1, while ‹ts› is 365 K as compared with 355 K, for the Nemethy-Scheraga and Planck-Benzinger model, respectively. At ‹tm›, the thermal agitation energy is about five times greater than ΔH°(T0) in the Planck-Benzinger model, that is 465 K compared to 497 K in the Nemethy-Scheraga model. The results imply that the negative Gibbs free energy minimum at a well-defined ‹ts›, where TΔS° = 0 at about 355 K, has its origin in the sequence-specific hydrophobic interactions, which are highly dependent on details of molecular structure. The Nemethy-Scheraga model shows no evidence of the thermodynamic molecular switch that we have found to be a universal feature of biological interactions. The Planck-Benzinger method is the best known for evaluating the innate temperature-invariant enthalpy, ΔH°(T0), and provides for better understanding of the heat of reaction for biological molecules.